Autoimmune disorders and paraneoplastic syndromes in thymoma - Blum, Torsten Gerriet (J Thorac Dis, 2020)
Thymomas are counted among the rare tumour entities which are associated with autoimmune disorders (AIDs) and paraneoplastic syndromes (PNS) far more often than other malignancies. Through its complex immunological function in the context of the selection and maturation of T cells, the thymus is at the same time highly susceptible to disruptive factors caused by the development and growth of thymic tumours. These T cells, which are thought to develop to competent immune cells in the thymus, can instead adopt autoreactive behaviour due to the uncontrolled interplay of thymomas and become the trigger for AID or PNS affecting numerous organs and tissues within the human body. While myasthenia gravis is the most prevalent PNS in thymoma, numerous others have been described, be they related to neurological, cardiovascular, gastrointestinal, haematological, dermatological, endocrine or systemic disorders. This review article sheds light on the pathophysiology, epidemiology, specific clinical features and therapeutic options of the various forms as well as courses and outcomes of AID/PNS in association with thymomas. Whenever suitable and backed by the limited available evidence, the perspectives from both the thymoma and the affected organ/tissue will be highlighted. Specific issues addressed are the prognostic significance of thymectomy on myasthenia gravis and other thymoma-associated AID/PND and further the impact and safety of immunotherapies on AID and PND relating to thymomas.